Brown spider phospholipase‐D containing a conservative mutation (D233E) in the catalytic site: Identification and functional characterization. Issue 11 (13th September 2013) - Vuitika, Larissa; Gremski, Luiza Helena; Belisário‐Ferrari, Matheus Regis; Chaves‐Moreira, Daniele; Ferrer, Valéria Pereira; Senff‐Ribeiro, Andrea; Chaim, Olga Meiri; Veiga, Silvio Sanches
ABSTRACT Brown spider (Loxosceles genus) bites have been reported worldwide. The venom contains a complex composition of several toxins, including phospholipases‐D. Native or recombinant phospholipase‐D toxins induce cutaneous and systemic loxoscelism, particularly necrotic lesions, inflammatory response, renal failure, and hematological disturbances. Herein, we describe the cloning, heterologous expression and purification of a novel phospholipase‐D toxin, LiRecDT7 in reference to six other previously described in phospholipase‐D toxin family. The complete cDNA sequence of this novel brown spider phospholipase‐D isoform was obtained and the calculated molecular mass of the predicted mature protein is 34.4 kDa. Similarity analyses revealed that LiRecDT7 is homologous to the other dermonecrotic toxin family members particularly to LiRecDT6, sharing 71% sequence identity. LiRecDT7 possesses the conserved amino acid residues involved in catalysis except for a conservative mutation (D233E) in the catalytic site. Purified LiRecDT7 was detected as a soluble 36 kDa protein using anti‐whole venom and anti‐LiRecDT1 sera, indicating immunological cross‐reactivity and evidencing sequence‐epitopes identities similar to those of other phospholipase‐D family members. Also, LiRecDT7 exhibits sphingomyelinase activity in a concentration dependent‐manner and induces experimental skin lesions with swelling, erythema and dermonecrosis. In addition, LiRecDT7 induced a massive inflammatory response in rabbit skin dermis, which is a hallmark of brown spider venom phospholipase‐D toxins. Moreover, LiRecDT7 induced in vitro hemolysis in human erythrocytes and increased blood vessel permeability. These features suggest that this novel member of the brown spider venom phospholipase‐D family, which naturally contains a mutation (D233E) in the catalytic site, could be useful for future structural and functional studies concerning loxoscelism and lipid biochemistry. Highlights: 1‐ Novel brown spider phospholipase‐D recombinant toxin contains a conservative mutation (D233E) on the catalytic site. 2‐LiRecDT7 shares high identity level with isoforms of Loxosceles genus. 3‐LiRecDT7 is a recombinant protein immunodetected by specific antibodies to native and recombinant phospholipase‐D toxins. 4‐LiRecDT7 shows sphingomyelinase‐D activity in a concentration‐dependent manner, but less intense than other isoforms. 5‐LiRecDT7 induces dermonecrosis and inflammatory response in rabbit skin. 6‐LiRecDT7 increases vascular permeability in mice. 7‐LiRecDT7 triggers direct complement‐independent hemolysis in erythrocytes. J. Cell. Biochem. 114: 2479–2492, 2013. © 2013 Wiley Periodicals, Inc.